REKONSTRUKSI KEDUDUKAN HUKUM SITA JAMINAN DALAM SISTEM HUKUM ACARA PERDATA INDONESIA - Alvarindo, Arif; Ahyar Wiraguna, Sidi (Penerbit Lafadz Jaya, 2025)
The rapid growth of digital economy in Indonesia has introduced new forms of wealth such as cryptocurrencies, NFTs, and electronic financial instruments, necessitating updates to conservatory attachment (sita jaminan) under colonial-era HIR Article 227 and RBG Article 261 to prevent asset dissipation in civil disputes. This normative juridical research aims to reconstruct the legal position of conservatory attachment for modern assets. Population comprises civil procedure norms (1920-2025); purposive sample includes 35 primary sources like HIR/RBG provisions, OJK regulations, and 15 SINTA-accredited journals. Instruments encompass primary legislation and secondary doctrines; data analyzed via conceptual, grammatical, systematic, and teleological interpretation with comparative approach. Findings reveal inconsistent judicial application, evidentiary gaps for digital assets, and regulatory obsolescence against non-physical property transfers. Conclusion recommends legislative replacement of HIR/RBG with Mahkamah Agung guidelines on blockchain forensics, prima facie standards, and proportional safeguards to ensure legal certainty and execution efficiency.